System view on the development of operation support information solutions - Калмыков, Андрей Викторович; Воскобойник, Олег Николаевич (Eastern-European Journal of Enterprise Technologies, 2011)
The article considers research points of modern methodologies in the area of the development and deployment of IT solutions in a complex environment. It proposes the system view on the design tasks space. The sequence of design actions for the refinement of system boundaries within the NGOSS life cycle has been proposed.